A Novel Approach for a Novel Pathogen: Using a Home Assessment Team to Evaluate Patients for COVID-19. (12th March 2020) - Bryson-Cahn, Chloe; Duchin, Jeffrey; Makarewicz, Vanessa A; Kay, Meagan; Rietberg, Krista; Napolitano, Nathanael; Kamangu, Carole; Dellit, Timothy H; Lynch, John B
Abstract: Thousands of people in the United States have required testing for SARS-CoV-2. Evaluation for a special pathogen is resource intensive. We report an innovative approach to home assessment that, in collaboration with public health, enables safe evaluation and specimen collection outside the healthcare setting, avoiding unnecessary exposures and resource utilization.